Alkynes From Furans: A General Fragmentation Method Applied to the Synthesis of the Proposed Structure of Aglatomin B. (28th February 2018) - Deng, Jiachen; Wu, Jingjing; Tian, Hailong; Bao, Jiajing; Shi, Yong; Tian, Weisheng; Gui, Jinghan
Abstract: Furans are versatile synthons in organic chemistry. Described is a general method for transforming furans into alkynes by dual C−C double‐bond cleavage. The reaction is proposed to proceed by sequential [4+2] cycloaddition between furan and singlet oxygen and a formal retro‐(3+2) fragmentation of the endoperoxide intermediate. A wide array of furans, including those derived from sapogenins, are amenable to this reaction, thus providing the corresponding alkynoic acids in up to 88 % yields. The synthetic utility was demonstrated by a seven‐step synthesis of the proposed structure of a pregnane natural product, aglatomin B, from a known intermediate.